THE EFFECT OF REPLACING COMMERCIAL RATIONS WITH CRICKET FLOUR (Gryllus mitratus Burm) ON BROILER CARCAS CUTS - D.W.B., Gurning,; Astawa, I P. A.; Puspani, E. (Jurnal Peternakan Tropika, 2024)
Broilers are chickens that genetically grow very fast have a high ability to convert food into meat, their growth is very fast from the age of 1-5 weeks. This study aims to determine the effect of replacing commercial rations with cricket flour ( Gryllus mitratus Burm ) on broiler carcass cuts. This research was conducted for 24 days at Sesetan Field Laboratory, Faculty of Animal Husbandry, Udayana University, Denpasar, Bali. The design used in this study was a completely randomized design (CRD) consisting of 4 treatments and 4 replicates, and each replicate used 4 broilers so that the total number of broilers used was 64. The treatments given are: P0: commercial ration without being replaced with cricket flour; P1: 2% commercial ration replaced with cricket flour; P2: 4% commercial ration replaced with cricket meal; and P3: 6% commercial ration replaced with cricket meal. The observed variables included slaughter weight, carcass percentage, breast percentage, back percentage, wing percentage, thigh percentage. The results showed that broilers that received commercial ration replacement with cricket flour as much as 2%, 4%, and 6% (P1, P2, and P3) had a significant effect (P <0.05) on carcass percentage, but had no significant effect (P>0.05) on the composition of carcass pieces The results of this study can be concluded that the replacement of commercial rations with cricket flour ( Gryllus mitratus Burm ) level 2, 4%, 6% is able to increase the percentage of carcasses and does not affect the composition of carcass pieces.